Optimalisasi Pemanfaatan Material Furnitur dalam Desain Interior Berkelanjutan - Paryoko, Vijar Galax Putra Jagat; Rachman, Raden Ayu Firdausi Novira (Waca Cipta Ruang, 2023)
The interior industry is one of few surviving sector during recent pandemic. A lot of materials are demanded to produce furniture and other interior components in this industry, it became a concern for sustainable development which has been an emphasis on design since 2000s and even more after the outbreak of the pandemic. Therefore, this research was conducted to find the optimizing steps of material utilization which can be carried on the policy, design, until production stages. Simulation methods is the main strategy of this research which is supported by literature review method. Concluded that choosing multiplex as main material is highly supporting the sustainable development because of its raw materials, manufacturing, until design phase concern. By utilizing this kind of materials, it was found that there is some design of dimension of certain furniture’s components that are considered efficient enough to be applied.